Juridical Review on Restrictions of Internet Access by Governments in Human Rights Perspective (Case Study of Jakarta Administrative Court Decision Number: 230/G/TF/2019/PTUN-JKT) - Okviani Assa Anggraini; Emy Rosnawati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to find out whether the judge's decision number 230/G/TF/2019/PTUN-JKT is in accordance with human rights regulations and also to find out whether internet access rights are part of human rights. The research method that the author uses is a normative juridical approach using a case approach or commonly known as the case approach. The conclusion of this study explains that internet access rights are part of Human Rights (HAM) because they both contain elements of freedom of expression and seek, convey and receive information without any restrictions. If there is a policy that limits internet access rights, then the policy is the same as limiting Human Rights and the policy can be said to be a violation of Human Rights. In decision number 230/G/TF/2019/PTUN-JKT, the Panel of Judges concluded that the actions of the defendants constituted a limitation on Human Rights (HAM) and that the action contained legal void so that the Panel of Judges decided that the action was against the law.